2017
DOI: 10.1111/jse.12247
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary species‐level phylogeny of the alpine ginger Roscoea: Implications for speciation

Abstract: Speciation, the evolutionary process forming new species, is a key mode generating biodiversity on the Earth. In this study, we produced a species‐level phylogeny of Roscoea using one nuclear ribosomal and two chloroplast DNA fragments based on Bayesian inference and maximum likelihood. We then explored the possible speciation processes using the species‐level phylogeny and the heterozygous sites in the nuclear DNA. The incongruence between nuclear and chloroplast phylogenies, and several heterozygous sites in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 56 publications
1
21
0
1
Order By: Relevance
“…These results suggest that Roscoea species are sensitive to climate change, providing an interesting case for integrative studies of climate drivers of genetic diversity. R. humeana is an herb endemic to the Hengduan Mountains (Cowley, 2007;Zhao, Gugger, et al, 2016;Zhao et al, 2017). Despite having a long floral tube, this species is pollinated by bees (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that Roscoea species are sensitive to climate change, providing an interesting case for integrative studies of climate drivers of genetic diversity. R. humeana is an herb endemic to the Hengduan Mountains (Cowley, 2007;Zhao, Gugger, et al, 2016;Zhao et al, 2017). Despite having a long floral tube, this species is pollinated by bees (Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The distribution range of R. tibetica has been considered to extend into the Himalayas, albeit obscured by the Himalayan species R. alpina Royle and R. bhutanica Ngamriab Cowley et al, 2007). However, phylogenetic reconstruction suggested that R. tibetica was not present in the Himalayas and that R. alpina and R. bhutanica were not present in the Hengduan Mountains Zhao et al, 2016bZhao et al, , 2017. Moreover, R. tibetica with typical taxonomic traits was separated from other Roscoea species, such as distant clades R. scillifolia (Gagnepain) Cowley and R. schneideriana (Loesener) Cowley (Zhao et al, 2017).…”
Section: Introductionmentioning
confidence: 98%
“…However, phylogenetic reconstruction suggested that R. tibetica was not present in the Himalayas and that R. alpina and R. bhutanica were not present in the Hengduan Mountains Zhao et al, 2016bZhao et al, , 2017. Moreover, R. tibetica with typical taxonomic traits was separated from other Roscoea species, such as distant clades R. scillifolia (Gagnepain) Cowley and R. schneideriana (Loesener) Cowley (Zhao et al, 2017). Floras proposed that current R. tibetica plants contains three synonyms, namely R. intermedia Gagnepain var.…”
Section: Introductionmentioning
confidence: 99%
“…Roscoea is a perennial deciduous genus that contains approximately 20 species, which are divided into ~8 species in the Himalayas and ~12 species in the Hengduan Mountains/Yun‐Gui Plateau, with some partially distributed in the north of Indochina, by an ~500‐km wide gap (Figure ), which is simply referred to as ‘Gap’ in this paper. These two groups of Roscoea are reciprocal monophyly (Ngamriabsakul et al, ; Zhao, Xia, et al, ; Zhao et al, ). Biogeographical reconstruction has suggested that the formation of the disjunction of Roscoea is likely caused by a rapid lateral extrusion of Indochina with the rapid uplift of the Himalayas during the early Miocene (approximately 23 Ma) and limited seed dispersal by ants (Ding et al, ; Zhao, Xia, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Roscoea is the only genus in the ginger family (Zingiberaceae) that has a regional disjunction in alpine regions (Cowley, 2007;Ngamriabsakul, Newman, & Cronk, 2000;Zhao, Xia, Cannon, Kress, & Li, 2016;Zhao, Zhong, Fan, Xia, & Li, 2017). Roscoea is a perennial deciduous genus that contains approximately 20 species, which are divided into ~8 species in the Himalayas and ~12 species in the Hengduan Mountains/Yun-Gui Plateau, with some partially distributed in the north of Indochina, by an ~500-km wide gap (Figure 1), which is simply referred to as 'Gap' in this paper.…”
Section: Introductionmentioning
confidence: 99%